A new species and new records of Oiovelia (Heteroptera: Gerromorpha: Veliidae) from Brazil - Rodrigues, Higor D. D.; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2016)
Oiovelia currently comprises eight species and has been recorded only from South America. Here, the ninth species, Oiovelia machadoi sp. nov. (Holotype male deposited in MZUSP: BRAZIL, São Paulo State, Biritiba Mirim, Parque Estadual da Serra do Mar, 23°42’16.4”S, 46°02’42.8”W, 725 m a.s.l., 23.VIII.2014, H. Rodrigues leg.), is described and illustrated based on specimens from the Atlantic Forest, Southeastern Brazil. The new species can be distinguished from all other species in this genus mainly by the dark color of the body, absence of the V-shaped pruinosity on the posterior lobe of pronotum, well-defined pruinosity between the cells of the forewing, and presence of a pair of spines on the proctiger. In addition, important intraspecific variations in a population of O. brasiliensis from the State of São Paulo are presented. Finally, the genus is recorded for the first time from Northeastern Brazil based on specimens of O. cunucunumana and O. viannai collected in the State of Bahia.